1998
DOI: 10.1017/s0043174500090883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corn (Zea mays) population and row spacing on corn and velvetleaf (Abutilon theophrasti) yield

Abstract: Research was conducted to determine the optimum population and row spacing for corn production and for suppressing velvetleaf growth and seed production. Corn was grown in a factorial arrangement of three populations targeted at 64,000 (1 ×), 96,000 (1.5 ×), or 128,000 (2 ×) plants ha−1and two row spacings of 38 or 76 cm. Influences on corn were determined in weed-free plots, and influences on velvetleaf were determined for target plants established at 1.5–m intervals along the center of corn interrows. Four v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 24 publications
5
42
1
1
Order By: Relevance
“…This definition was subsequently broadened to include effects on other organisms, including microorganisms in particular. Once the weed seedlings become established, competition for resources is the main mechanism of weed suppression by the cover crop (Teasdale 1998;Hollander et al 2007b). However, it is difficult to distinguish experimentally between allelopathy and mechanisms involving competition for growth resources.…”
Section: Effect Of a Cover Crop On Weed Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition was subsequently broadened to include effects on other organisms, including microorganisms in particular. Once the weed seedlings become established, competition for resources is the main mechanism of weed suppression by the cover crop (Teasdale 1998;Hollander et al 2007b). However, it is difficult to distinguish experimentally between allelopathy and mechanisms involving competition for growth resources.…”
Section: Effect Of a Cover Crop On Weed Communitiesmentioning
confidence: 99%
“…However, the major obstacle to the adoption and use of living mulches is their lack of selectivity: a living mulch that is competitive enough to suppress weeds may also decrease crop growth and yield, although this does not occur in all cases (Ateh and Doll 1996). Much of the research on living mulches has focused on developing approaches for achieving selectivity between weeds and the associated crop, including (a) sowing the living mulch so that its peak growth does not occur during the period in which competition would have the greatest impact on crop yield, (b) increasing the density of the crop population to increase the competitiveness of the crop relative to the living mulch, (c) suppressing the living mulch during crop growth so as to make it less competitive with the crop (Teasdale 1998;Teasdale et al 2007;Hollander et al 2007b). …”
Section: Effect Of a Cover Crop On Weed Communitiesmentioning
confidence: 99%
“…However, the study did not directly compare 76 em rows to 38 em rows at the same plant density. Conversely, in a more recent study, Teasdale ( 1998) did not find any difference in the effect of row spacing on Abutiton theophrasti growth and survival. reported that com sown in a rectangular plant aiTangement (51 em row spacing) had little effect on Setaria faberi and Ambrosia artemisifolia control and that cultivation was the most important factor for the successful use of reduced herbicide rates.…”
Section: Introductionmentioning
confidence: 62%
“…But, the effect of the planting pattern on the weed biomass production was not significant at any level of weed density at the corn silking stage (Table 2). Also, Teasdale (1998) showed row spacing had little or no effect on the biomass and seed production of velvetleaf ( Abutilon theophrasti L.). Another similar study also reported that less row spacing reduced the biomass of late‐emerging annual weeds (Murphy et al .…”
Section: Resultsmentioning
confidence: 99%
“…2005). The growth and fecundity of most plants depends on their density, so increasing the crop density would affect the potential growth and seed production of crops and weeds in cropping systems (Teasdale 1998; Baghestani et al . 2006a).…”
Section: Introductionmentioning
confidence: 99%